2013
DOI: 10.1128/genomea.00951-13
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Analysis of Influenza B Viruses of Multiple Genotypes Cocirculating in India

Abstract: Systematic influenza virus surveillance has been carried out in India since 2004 and has revealed the cocirculation of type B lineages. The genetic diversity of influenza B viruses was observed when full-genome analysis was performed. In 2010, the cocirculation of multiple genotypes was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Furthermore, phylogenetic analysis of the NS gene showed that all viruses clustered together to form a distinct Lineage IV. The incongruent phylogenetic patterns observed at the lineage level corroborated with previous reports [ 7 , 13 , 15 , 16 ], which suggest that the phylogenies of eight gene segments could be divided into three distinct evolutionary profiles: (i) PB1, PB2 and HA genes derived from either Lineage II or III; (ii) PA, NP, NA and MP genes derived from Lineage II; and (iii) NS genes derived from Lineage IV. Firstly, the consistent grouping of Yam-like or Vic-like viruses in Lineage II or III, respectively, in the tree topology of PB1, PB2 and HA genes could be attributed to possible genetic linkage between these three gene segments, which has been described [ 8 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, phylogenetic analysis of the NS gene showed that all viruses clustered together to form a distinct Lineage IV. The incongruent phylogenetic patterns observed at the lineage level corroborated with previous reports [ 7 , 13 , 15 , 16 ], which suggest that the phylogenies of eight gene segments could be divided into three distinct evolutionary profiles: (i) PB1, PB2 and HA genes derived from either Lineage II or III; (ii) PA, NP, NA and MP genes derived from Lineage II; and (iii) NS genes derived from Lineage IV. Firstly, the consistent grouping of Yam-like or Vic-like viruses in Lineage II or III, respectively, in the tree topology of PB1, PB2 and HA genes could be attributed to possible genetic linkage between these three gene segments, which has been described [ 8 ].…”
Section: Resultssupporting
confidence: 89%
“…In conclusion, this present study highlights the strategy used for the phylogenetic classification of all gene segments of influenza B viruses, which classifies all genes at the lineage, clade and sub-clade level. This strategy for lineage classification was adapted from previously reported methods [ 7 , 13 , 15 , 16 ], while the strategy for clade and sub-clade classification was adapted from the WHO interim reports [ 11 , 12 ] and criteria used for H5N1 classification [ 30 ], respectively. Adaptation of this approach in future studies with a larger dataset of whole-genome sequences may perhaps allow a better understanding of the complexity of segment reassortments in influenza B evolution which may contribute to future vaccine design, and also for better monitoring of unique reassortants in surveillance studies.…”
Section: Resultsmentioning
confidence: 99%
“…49 In our study, both Yamagata and Victoria lineage strains of influenza B were found in this region, similar to other reports of co-circulation of both the lineages from India, China and Singapore. [50][51][52] Globally, Victoria lineage of influenza B viruses is considered the predominant type of influenza B viruses 53 and the current influenza vaccine contains only the Victoria-like lineage virus (B/Brisbane/60/ 2008). However, previous studies conducted in humans have proved that this vaccine could not provide immunity against the Yamagata lineage viruses 54 and hence recently, CDC has approved the usage of Quadrivalent vaccine with both the types of influenza B viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this study various studies are being carried out in India. The National Institute of Virology has continued research work on isolation, genetic characterization and drug susceptibility monitoring of pdmH1N1 isolates from India under national surveillance program as well as [12] which revealed the co-circulation of type B lineages. The genetic diversity of influenza B viruses was observed when full-genome analysis was performed.…”
Section: Rt-pcr Methodsmentioning
confidence: 99%
“…Annual influenza epidemics are responsible for the death of 250,000-500,000 people worldwide and cause illness in (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) % of the total population each year [22]. Human influenza occurs all over the world with annual global attack rate of fever or myalgia, headache, malaise or non productive cough.…”
Section: Introductionmentioning
confidence: 99%